Identification of Cultivable Bacteria from Tropical Marine Sponges and Their Biotechnological Potentials - Tan Suet May Amelia,; Al-Ashraf Abdullah Amirul,; Jasnizat Saidin,; Kesaven Bhubalan, (Tropical Life Sciences Research, 2018)
Marine sponges are acknowledged as bacterial hotspots in the oceanic biome. Aquatic bacteria are being investigated comprehensively for bioactive complexes and secondary metabolites. Cultivable bacteria associated with different species of sea sponges in South China Sea waters adjacent to Bidong Island, Terengganu were identified. Molecular identification was accomplished using 16S rRNA gene cloning and sequencing. Fourteen bacterial species were identified and their phylogenetic relationships were analysed by constructing a neighbour-joining tree with Molecular Evolutionary Genetics Analysis 6. The identified species encompassed four bacterial classes that were Firmicutes, Actinobacteria, Alphaproteobacteria and Gammaproteobacteria known to have been associated with sponges. The potential biotechnological applications of the identified bacteria were compared and reviewed based on relevant past studies. The biotechnological functions of the 14 cultivable isolates have been previously reported, hence reinforcing that bacteria associated with sponges are an abundant resource of scientifically essential compounds. Resilience of psychrotolerant bacteria, Psychrobacter celer, in warm tropical waters holds notable prospects for future research. Span laut diakui sebagai titik panas bakteria di bioma samudera. Bakteria akuatik sedang diselidiki secara komprehensif untuk kompleks bioaktif dan metabolit sekunder. Bakteria yang boleh dikulturkan dikenal pasti dari spesies span laut berlainan di perairan Laut China Selatan berdekatan Pulau Bidong, Terengganu. Pengenalpastian molekul dicapai dengan pengklonan dan penjujukan gen 16S rRNA. Empat belas spesies bakteria telah dikenalpasti dan hubungan filogenetik mereka telah dianalisis dengan membina pokok neighbour-joining menggunakan Molecular Evolutionary Genetics Analysis 6. Spesies yang dikenal pasti merangkumi empat kelas bakteria yang pernah dikaitkan dengan span, iaitu kelas Firmikuta, Aktinobakteria, Alfaproteobakteria dan Gammaproteobakteria. Aplikasi bioteknologi bakteria yang dikenal pasti telah dibandingkan dan diulaskan berdasarkan kajian lepas yang berkaitan. Fungsi bioteknologi 14 isolat kultivar telah dilaporkan sebelum ini, justeru meyakinkan bahawa span adalah sumber kaya dengan bahan-bahan yang penting dari segi saintifik. Kewujudan bakteria psikotoleran Psychrobacter celer di perairan tropika yang hangat memiliki prospek ketara untuk penyelidikan masa depan.